Recurrent pseudoprogression in isocitrate dehydrogenase 1 mutant glioblastoma - Kebir, Sied; Giordano, Frank Anton (Journal of clinical neuroscience, 2018)
In a subset of glioblastoma (GBM) patients, the differentiation between tumor progression and tumor pseudoprogression (PsP) is challenging. This case describes a male patient suffering from isocitrate dehydrogenase 1 (IDH1) mutant GBM who demonstrated an increasing contrast-enhancing (CE) lesion on a cranial magnetic resonance imaging (cMRI) scan 8months after radiochemotherapy. In accordance with the response assessment in neuro-oncology (RANO) criteria, the cMRI lesion was classified as recurrent tumor, although 18F-fluoroethyl-L-tyrosine positron emission tomography (18F-FET-PET) did not indicate vital tumor tissue. The patient underwent re-surgery but histopathology only revealed reactive and necrotic tissue, consistent with PsP. Nine weeks after complete resection of the CE lesion, a new lesion emerged that later regressed in the follow-up cMRI scans, thereby retrospectively establishing the diagnosis of recurrent PsP.